Teaching-learning model of muchik language and waist weaving - Palomino Acuña, Andrea Leoncia (2015)
In this paper it is proposed a teachinglearning model and waist waving whose aim is strengthens the cultural identity in teachers and students of the High Schools in Mochumí disctrict because through the ethnographic observation and application of interviews, it shows that teachers do not practice or transmit to future generations the Muchik language, the waist waving and aspects pertaining to their ancestral culture. Students do not know about their heritage. They believe the Lord of Sipán spoke Quechua and not the Muchik; they do not know that our ancestors made their clothes through the weaving waist technique which is still practiced. Faced with this problem, it was set out to design and propose this proactive-descriptive model through an appropriate theoretical foundation which was presented to teachers in the sample group through a focus group in order to gather their opinions about the model which was presented to 5 experts to be validated by the individual aggregated method.